Bauman, Freire and the ambivalence of education in (post)modernity (Práxis Educativa, 2025)
The dialogue between Zygmunt Bauman’s Liquid Modernity and Paulo Freire’s political and epistemological stance provides the basis for a theoretical reflection on the thought of both authors on the social context of modernity and its impact on education the educational field at the end of the 20th century, offering insights into the challenges at the threshold of the 21st century. Thus, this discussion aims to discuss some thematic nuclei of these authors, exploring intersections that reveal a common societal project in defense of a critical, humanistic, and democratic education. In particular, this theoretical reflection introduces the concept of ambivalence as a key element for building theoretical frameworks that enable the problematization of the instrumental character of education in modernity, recognizing the disputed field concerning the (post)modern societal project.Keywords: Zygmunt Bauman. Paulo Freire. Ambivalence.